2011
DOI: 10.1017/s0021932011000265
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Multi-Dimensional Knowledge Deprivation of Hiv/Aids: A New Approach With Indian Evidence on Its Magnitude and Determinants

Abstract: Though HIV/AIDS poses serious risks to economic security, there is very little economics literature quantifying awareness and knowledge of this disease and their principal socioeconomic determinants. This is what the present study attempts to do in the context of India, which faces a significant threat from HIV/AIDS. The study is based on India's National Family Health Surveys covering the period of economic reforms and beyond. The contribution is both methodological and empirical. The study shows that the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The measure of knowledge Following an earlier study (Ray & Sinha, 2010), this study distinguishes between HIV awareness and knowledge. An individual may be aware of HIV but may not know much of the true nature of the disease.…”
Section: Methods and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The measure of knowledge Following an earlier study (Ray & Sinha, 2010), this study distinguishes between HIV awareness and knowledge. An individual may be aware of HIV but may not know much of the true nature of the disease.…”
Section: Methods and Datamentioning
confidence: 99%
“…The reader is referred to Ray & Sinha (2010) for further details. ignorance, of the true nature of HIV.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Separation from families, flourishing sex trade, marriages at a later age and availability of money from employment provide opportunities for sexual encounters with multiple partners–both commercial and non-commercial [35, 36, 52]. These conditions coupled with lack of information about HIV prevention and condoms might increase the risk of unsafe sex and chances of HIV acquisition [17, 39, 51]. Overcrowded urban areas also known to have concentrations of other HRGs like FSW, MSM etc., which can further fuel the HIV epidemic in these districts [4, 5, 54, 55].…”
Section: Discussionmentioning
confidence: 99%
“…Studies done in different parts of India had shown the association of lower literacy, higher urbanisation and socio-economic development with higher HIV prevalence levels [27, 28, 32, 34–37]. Other studies have also brought out low levels of HIV awareness and condom use in India [17, 38, 39]. However, most of these studies have been carried out in one or few states of India, and there has been no study at the national level to understand the relationships of socio-demographic factors with HIV in India.…”
Section: Introductionmentioning
confidence: 99%